2007
DOI: 10.1002/bip.20897
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of the ΔPhe or ΔAla residue and the p‐nitroanilide group on a didehydropeptides conformation

Abstract: Two series of dehydropeptides of the general formulae Boc-Gly-X-Phe-p-NA, Boc-Gly-Gly-X-Phe-p-NA, Gly-X-Gly-Phe-p-NA.TFA, and Boc-Gly-X-Gly-Phe-p-NA, with X = Delta(Z)Phe and DeltaAla, were studied with NMR in DMSO and CDCl(3)-DMSO, and with CD in MeOH, MeCN, and TFE. The NMR spectra measured in DMSO suggest that peptides with the DeltaPhe residue next to Phe are folded whereas peptides with Gly between DeltaPhe and Phe are less ordered. NMR spectra of DeltaAla-containing peptides indicate that these peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 82 publications
(114 reference statements)
1
16
0
Order By: Relevance
“…2) in the near-UV in MeOH, TFE, and MeCN show that the peptide adopts the type II β-turn conformation at the Gly 1 and ∆ Z Phe 2 residues, stabilized by the intramolecular hydrogen bond between the amide proton of Gly 3 and the carbonyl oxygen of the Boc group. 18 The presence of such a conformation is consistent with the NMR studies which show that the Gly 3 amide proton is involved in a hydrogen bond (Table II) and by the conformational calculations (Table V). The analogous reasoning as in the case of Z-OMe indicates that there is another β-turn, either at the ∆ Z Phe 2 and Gly 3 or Gly 3 and Phe 4 residues, stabilized by the corresponding 4→1 hydrogen bond.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…2) in the near-UV in MeOH, TFE, and MeCN show that the peptide adopts the type II β-turn conformation at the Gly 1 and ∆ Z Phe 2 residues, stabilized by the intramolecular hydrogen bond between the amide proton of Gly 3 and the carbonyl oxygen of the Boc group. 18 The presence of such a conformation is consistent with the NMR studies which show that the Gly 3 amide proton is involved in a hydrogen bond (Table II) and by the conformational calculations (Table V). The analogous reasoning as in the case of Z-OMe indicates that there is another β-turn, either at the ∆ Z Phe 2 and Gly 3 or Gly 3 and Phe 4 residues, stabilized by the corresponding 4→1 hydrogen bond.…”
Section: Discussionsupporting
confidence: 87%
“…It has been found that in the solid state a ∆Phe residue of the Z configuration induces β-turns in short sequences [2][3][4][5][6] and a 3 10 -helix in longer ones or peptides with more than one dehydro residue. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19] Similar conformational properties of ∆ Z Phe have been observed in solution by NMR 8,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and CD, 18,19,[27][28][29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…This is strongly dependent on the peptide conformation and therefore very useful in this kind of conformational studies. 21 The CD spectra obtained in three solvents for peptides no. 1 and no.…”
Section: Spectroscopymentioning
confidence: 99%